Criteria applied in the definition of influence areas, impacts and programmes in environmental impact studies of Brazilian hydroelectric power plants - Carvalho, Dayane Nayara [UNESP]; Boniolo, Milena Rodrigues [UNESP]; Santos, Rafael Gonçalves [UNESP]; Batista, Ludmila Vianna [UNESP]; Malavazzi, André Aparecido [UNESP]; Reis, Fábio Augusto Gomes Vieira [UNESP]; Giordano, Lucilia Do Carmo [UNESP] (UNESP - Universidade Estadual Paulista, 2018)
The need to expand the energy supply in order to provide economic growth and development is a growing reality in Brazil. However, the expansion of energy generated from hydroelectric power plants is controversial due to its potentialities, generated impacts and methodologies applied in its licensing. Thus, this study sought, through bibliographical review and documentary analysis, to formulate a synthesis covering the main similarities and differences in Environmental Impact Studies of nine different hydroelectric power plants projects. It was verified that the criteria applied in the definition of influence areas were similar in all studies analysed, especially between the physical and biotic environments. It was also observed high number of impacts during the implementation and operation phase of these projects, indicating the need for greater attention to environmental programmes and the measures adopted in these phases. The difference in reported frequency of some impacts reflects the relationship they have with local features of the region. It was also verified lack of standardisation in the definition of influence areas and evaluation methods of the impacts analysed. Therefore, this article contributes to the discussion of the criteria adopted in the elaboration of Environmental Impact Studies of hydroelectric power plants.
Critérios usados na definição de áreas de influências, impactos e programas ambientais em estudos de impacto ambiental de usinas hidrelétricas Brasileiras
Keywords: EIA; Environmental impact studies; Hydroelectric power plant; Influence areas